Poetics of the Changing Dunescape: turning Brownfield Terrain into Activity and Ecological Open Space - Kulikovskaya, Maria (School of Architecture, Planning and Geomatics, 2021)
Our environment and our perception of it are continuously changing. This thesis objective is to change an existing site to become an experientially poetic landscape, imbued with meaning, a strong sense of place, presence and belonging. It explores the ideas of palimpsest, theory of place and experiential landscape architecture. The argument is that only through physical, bodily engagement with the landscape may it acquire meaning in the collective memory and significance as a place, especially when informed by the unique characteristics of the site itself. The site is positioned in Wingfield/Maitland, an under-appreciated, derelict, forgotten and currently nonexperiential large tract of land, lying in the Cape Flats area. The land is under a threat of re- development, with existing proposals intending to develop it to its maximum extent, not taking sufficient cognisance of its other values. This is a good case for when a landscape architectural approach may look at the site from a more holistic point of view, taking into account the various values, needs and claims of the site. Landscape in this project is understood to be a cultural construct. The design takes inspiration from understanding the unique natural-cultural qualities of this land, which serve as a tool to create attachment to the place and to nature's rhythms. The change is a poetic event. Compared to the extremes of climate of my childhood and adolescence homeland, I find the change in the Cape Flats landscape to be more subtle, and it takes time to grow to appreciate its poetry. The idea of change is a multi-layered one. It is about the poetical seasonal and other cyclical changes between the dry and wet seasons, wind strength, and flooding, changing colours and shapes, and the necessity of periodic fires. I believe, change is also imperative in our attitude towards our engagement with and appreciation of the landscape. Change is about the evolution of the landscape and its history, and about its continuous and necessary adaption to future conditions, in terms of both environmental and future human needs. The site has undergone a lot of natural and anthropogenic alterations. The topic of poetic change is inspired by both the site's natural character and by its history. The change is explored in the design through the concepts of movement and participation in the landscape, allowing for experience of various conditions. It is also supported by the concept of connectivity, both natural and human; and the concepts of contrast and counterpoint; as well as the strategies of inclusion and absence. Water, sand, vegetation, as well as some traces of human activity, are the main place-making elements in the design. The inland dunes with mosaic wetland habitat and their associated vegetation are some of the last traces of the typical Cape Flats landscape, that was/is not fully understood or appreciated. These natural elements are the best expressions of the landscape's ephemerality, changeability and the sense of time. It is the breathtaking potential abundance and variety of life on this site that is the inspiration for this design thesis.